Domesticating fears and fantasies of 'the East': integrating the Ottoman legacy within European heritage. Issue 15 (12th October 2016) - Bryce, Derek; Čaušević, Senija
ABSTRACT: 'Europe' has no fixed geographical, historical, religious or cultural boundaries. Claims for the existence of European civilization as a discrete construct are continually made yet dissolve on close scrutiny. Here, we examine these claims at one of the grandest points of existential crisis and belonging for Europe, the relationship with the 'Other within': Turkey, the Balkans and Ottoman heritage in Europe. Through a hybrid semiotic and Foucauldian analysis of catalogues of eight high-profile exhibitions in the United Kingdom, Turkey, Belgium and Portugal we argue that an unsettled discursive struggle is at play, in which one 'Europe' articulates 'reconciliation' of profound civilizational difference while another, Ottoman, 'Europe' stakes a claim of right as an intrinsic component of what it means to be European in a contemporary context. We attempt to trace the role of museum marketing in the perennial accommodation/exclusion of the Ottoman Empire as an intrinsic component in the diversity of Europe's cultural heritage.